2011
DOI: 10.1016/j.bbrc.2011.06.176
|View full text |Cite
|
Sign up to set email alerts
|

α-Pinene isolated from Schinus terebinthifolius Raddi (Anacardiaceae) induces apoptosis and confers antimetastatic protection in a melanoma model

Abstract: Malignant melanoma is one the most aggressive types of cancer and its incidence has gradually increased in the last years, accounting for about 75% of skin cancer deaths. This poor prognosis results from the tumor resistance to conventional drugs mainly by deregulation of apoptotic pathways. The aim of this work was to investigate the cell death mechanism induced by α-pinene and its therapeutic application. Our results demonstrated that α-pinene was able to induce apoptosis evidenced by early disruption of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 31 publications
2
98
0
17
Order By: Relevance
“…Then, a-pinene is a natural compound present in the oils of many species of conifers, particularly pine trees 53 . It has been reported that a-pinene could be used for the therapy of melanoma due to its great potential to induce apoptosis on cancer cells 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Then, a-pinene is a natural compound present in the oils of many species of conifers, particularly pine trees 53 . It has been reported that a-pinene could be used for the therapy of melanoma due to its great potential to induce apoptosis on cancer cells 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with previous study (Wang et al 2012), which has reported that α-pinene and β-pinene isolated from Rosmarinus officinalis demonstrated strong cytotoxicity towards human ovarian cancer cell lines (SK-OV-3 and HO-8910) and human hepatocellular liver carcinoma cell line (Bel-7402) in the MTT in vitro assay. Also, Matsuo et al (2011) revealed that α-pinene was able to induce apoptosis evidenced by early disruption of the mitochondrial potential, production of reactive oxygen species, and increase in caspase-3 activity in B16F10 murine melanoma cell. An additional recent study indicated that terpinolene reduced the protein expression of AKT1 in K562 human leukemic cells and inhibited cell proliferation (Okumura et al 2012).…”
Section: Primary Rat Neuronsmentioning
confidence: 96%
“…Further, we did not test whether forest environment-induced tumor suppresconditions used here. Matsuo et al found that α-pinene induced apoptosis and inhibited metastasis in a melanoma model with a relatively high concentration of α-pinene (100 μg/mL = 100 mg/L) (14). In contrast, we used α-pinene at the very low concentration of 180 ng/L in air.…”
mentioning
confidence: 99%